CLUSTER ANALYSIS OF HUNGARIAN SSC AN EMPIRICAL RESEARCH STUDY - Róbert, Marciniak (European Scientific Journal, ESJ, 2015)
Shared services is an organizational model that aim to reorganize mostly the backoffice service functions and centralize them into an internal service delivery center. The shared service model reached a high popularity in the last in the whole world but there are some countries and regions that are more successful in it than others. Central-Eastern Europe and Hungary within it was very popular destination of new service delivery centers in the last decades. The relative proximity geographically, in time-zone, culture, language-knowledge and the availability of higher-educated and well-skilled workforce were the main drivers for the prominence of the region in the last decades. Hungary is the second most important country in the region in this shared service market. This research study aimed to disclose how it be possible to disclose the evaluating factors and based on it to categorize into clusters those shared service centers that are operating in the Hungarian shared service market.